The Center of Excellence in Atmospheric Science (2002-2019)-from molecular and biological processes to the global climate - Lintunen, Anna; Aalto, Juho; Asmi, Ari; Aurela, Mika; Bäck, Jaana; Ehn, Mikael; Ezhova, Ekaterina; Hakola, Hannele; Hartonen, Kari; Heinonsalo, Jussi; Hellén, Heidi; Hölttä, Teemu; et al. (Finnish Environment Institute, 2024)
The study of atmospheric processes related to climate requires a multidisciplinary approach, encompassing physics, chemistry, meteorology, forest science, and environmen-tal science. The Academy of Finland Centre of Excellence in atmospheric sciences (CoE ATM) responded to that need for 18 years and produced extensive research and eloquent results, which are summarized in this review. The work in the CoE ATM enhanced our understanding in biogeochemical cycles, ecosystem processes, dynamics of aerosols, ions and neutral clusters in the lower atmosphere, and cloud formation and their interactions and feedbacks. The CoE ATM combined continuous and comprehensive long-term in-situ observations in various environments, ecosystems and platforms, ground-and satellite -based remote sensing, targeted laboratory and field experiments, and advanced multi-scale modeling. This has enabled improved conceptual understanding and quantifications across relevant spatial and temporal scales. Overall, the CoE ATM served as a platform for the multidisciplinary research community to explore the interactions between the biosphere and atmosphere under a common and adaptive framework. Peer reviewed